Diseño de ruta agroturística como aporte al desarrollo del turismo sostenible desde el cantón Quevedo en la provincia de los Ríos hacia el cantón Pangua en la provincia de Cotopaxi - Moreira Icaza, Carmen Victoria (2018)
The design of the Agrotourism route in the Quevedo cantons of the province of Los Ríos and Pangua in the province of Cotopaxi, seeks the interaction of the economy and sustainability of the sectors involved and, therefore, improves the quality of life of all its inhabitants, this research raises the proposal of agro-tourism route design where it involves all the owners of the haciendas where this is developed due to the demands of the population in generating new sources of economic income and the local development of the area and thus improve the quality of life of the inhabitants. The present document analyzes in chapter 1 the information of international, national, local and institutional context with the support of theoretical foundations of other authors related to the variables of the research, the research objectives for its development, the general delimitation of the investigation, the problematic situation, the existing problems in the beginning for the development of the investigation. In chapter 2 the theoretical framework of application in the research is presented, citation of concepts of several authors that contribute to the research, defining the two variables of the research topic in which the related concepts are cited, finally we find references or investigative antecedents and the hypothesis and sub-hypothesis of the investigation. In the third Chapter the results of the research were developed with their respective data analysis with statistical graphs and the table of details which had a good result for the development of the research topic. In the fourth chapter, the theoretical proposal of the research is applied, giving solution to the problem and developing the theme of the agrotouristic route design with each one of its components for the development of the same, the route map was designed, 2 travel options are presented for it the tourist attractions that are close to the main authors are promoted, in this case the haciendas, the financing of the proposal and finally the expected results are obtained in the objectives to design the agrotourism route.